"Don't be alarmed. It's to do with sex." Sherlock Holmes fanfiction and freedom of the imaginary domain - Van der Nest, Megan (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2020)
In this thesis I argue that, for the individual fan, reading and writing fanfiction texts, and engaging with the online fandom communities within which these texts are produced, is a potentially valuable experience. This is because the kind of social and creative spaces found in these communities allow for, and celebrate, the free imaginative play with romantic and sexual desires, identities, and relationships. To articulate the importance of these spaces, I draw on Drucilla Cornell's concept of the imaginary domain, defined as the psychic space each individual uses to explore different sexual desires and personae, which exploration is necessary for the development of full personhood. I also argue that the growing visibility and influence of fandom in modern society means that it could serve as a mechanism for social change, particularly in the acceptance and support of multiple sexual identities and forms of love. Selected texts, drawn from the Sherlock fandom, are discussed as representative of the approach taken within fanfiction communities towards various aspects of sexuality and sexual ethics. This approach combines the enthusiastic exploration of sexual desires without shame or fear of judgment with an ongoing, critical interrogation of sexual ethics.
Keywords: Fan fiction; Fans (Persons) -- Fiction; Holmes, Sherlock; Literature and the internet; Sex in literature